Islamic Concept in the Architecture of the Saoraja Lapinceng Traditional House - Susmihara; Nur Fitri Awaliah Nur; Ummi Farhah (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2022)
The historic house of Saoraja Lapinceng was created in 1879 by Andi Muhammad Saleh Daeng Parani Arung Balusu, often known as King Balusu. When Saoraja Lapinceng was established, the building collapsed, shattering glassware such as plates and other kitchenware (in the Bugis language, pinceng means glass). Thus, it was given the name Soraja Lapinceng. The components of a traditional Soraja Lapinceng home are separated into three sections: rakkeang, ale bole, and awa bola. This research seeks to elucidate the relationship between Islam and the Barru community in the architecture of the traditional Saoraja Lapinceng house. Qualitative information derived from field and library studies. The researchers employed historical, archeological, social anthropological, and architectural methods to address these issues. Observation, in-depth interviews with homeowners, community leaders, and the community surrounding the traditional house, as well as the collection of papers and audio recordings, were the data gathering techniques utilized in this study. The results of the study indicate that the concept of Islam in the architecture of the traditional Saoraja Lapinceng house is reflected in the orientation of family furniture, particularly the bed, towards the Qibla. The bedrooms for children and parents are divided, and the bedrooms for boys and girls are also segregated. The water barrel is positioned adjacent to the site's entrance stairs so that those who wish to enter the residence can do so with clean feet. According to Islamic teachings, the home must be clean, and the water barrel is used to collect water for ablution. In accordance with Islamic principles, the toilet cannot face the Qibla. This conforms to the notion of including toilets in the spatial layout of a typical Saorja Lapinceng home. The goal of this study is for individuals to apply the ideals and values of Saoraja Lapinceng traditional house building to the contemporary period.